Designation of a Nano‐Fe3O4 Based Composite Electrode with Long Cycle Life for Lithium‐Ion Batteries. Issue 14 (18th April 2019) - Wu, Pengfei; Dong, Xichao; Gu, Chong; Ge, Shuaipeng; Su, Zhiming; Lu, Yingxi; Guo, Changqing; Shao, Guangyu; Zhong, Yunwang; Liu, Anhua
Abstract: In order to address the issue of large volume expansion and poor electrical conductivity of Fe3 O4 ‐based anodes for lithium‐ion batteries, carbon and SiOx /SiC heterojunction double‐shell coated Fe3 O4 (Fex Siy ) nanocomposites were synthesized by crosslinking, pyrolysis and decarbonization of sol particles. The particles were produced by the reaction of iron carbonyl with liquid polycarbosilane using pitch as isolator, which is a low cost and easy to scale up preparation method. It is found that the double‐shell structure of the nanoparticles not only solves the problem of comminution of Fe3 O4 during cycling, but also ensures stable cycling and superior rate performance. The FeOSiC‐30 anode delivers a high reversible capacity (1357.2 mAh g −1 for 550 cycles at 1 A g −1 and 1060.7 mAh g −1 for 2500 cycles at 5 A g −1 ). The excellent electrochemical performance can be contributed to the novel structure: 1) the uniform carbon layer can improve the electrical conductivity and ensure the formation of a stable SEI; 2) different active materials can relieve the stress caused by volume variation and also contribute additional capacity; 3) the small particle size can offer a strong kinetic of electrochemical reactions and lithium ion transfer. These results can strongly support the improvement of the capacity of Fe3 O4 ‐based anodes by the unique multi‐function structural design, also providing new pathways for the design of other electrode materials. Abstract : Double shelled anode : a double shelled nano‐Fe3 O4 based composite is prepared as electrode material for Li‐ion batteries. The double shell coating prevents aggregation and pulverization of the Fe3 O4 nanoparticles in the cycling process, and ensures the formation of a stable SEI film, improving the cyclic stability. SiOx and Fex Siy are introduced to increase the capacity at both, low and high current densities. These properties make these composites more competitive for further applications.